Geo-environmental zoning using physiographic compartmentalization: a proposal for supporting sustainable decision-making - Correa, Claudia V. S. [UNESP]; Reis, Fabio A. G. V. [UNESP]; Giordano, Lucilia C. [UNESP]; Bressane, Adriano [UNESP]; Chaves, Camila J. [UNESP]; Do Amaral, Ana Maria C. [UNESP]; Brito, Hermes D. [UNESP]; De Medeiros, Gerson A. [UNESP] (Acad Brasileira De Ciencias, 2017)
The geo-environmental zoning represents an important strategy in the territorial management. However, it requires a logical and structured procedure. Therefore, an approach using physiographic compartmentalization is proposed and applied as case study in a region covered by the topographic maps of Sao Jose dos Campos and Jacarei, Brazil. This region has great geological and geomorphological peculiarities, beyond being a place with large human interventions because of its quickly economic growth. The methodology is based on photointerpretation techniques and remote sensing in GIS environment. As a result, seven geo-environmental zones were obtained from a weighted integration by multicriteria analysis of physiographic units with land-use classes. In conclusion, taking into account potentialities and limitations, the proposed approach can be considered able to support sustainable decision-making, being applicable in other regions.
Keywords: remote sensing; decision-support; earth sciences; land use